Analisis Sisa Radiofarmaka Teknesium-99m MDP Pada Pemeriksaan Sidik Tulang Di Instalasi Kedokteran Nuklir - Darmawan, Nathania Anggi; Taat Guswantoro (Lembaga Pengembangan Kinerja Dosen, 2024)
Bone cancer that has metastasized can be detected through a bone fingerprint examination, which involves the injection of tc-99m with the pharmaceutical Methylene Diphosphate (MDP). Bone prints are often used to trigger possible metastases of cancer to the bone, which is a major health problem for women worldwide. This study aims to activate the described organ uptake and residual radiopharmaceuticals in bone prints using the Region of Interest (ROI) method. The research was conducted on five datasets of patients with breast cancer. The patient received an intravenous injection of tc-99m MDP and, three hours later, underwent a bone fingerprint examination with a gamma camera. The image results from the gamma camera were processed using the ROI technique and analyzed further using statistical methods. The research findings showed that the five patients experienced an average reduction in residual radiopharmaceuticals of 2.965945119 mCi. Several factors, such as examination time, radiopharmaceutical dose, and body metabolism, influence the decay of radioactive activity in the body. The calculation of the absorption percentage for the five patients showed variations between 0.190070697% and 0.3510157519%